Answers

2015-01-14T12:13:16+05:30
A²b²-c²  = (ab)²-(c)²=(ab+c)(ab-c)
25(x+y)²-9(x-y)²=(5x+5y)²-(3x-3y)²=(5x+5y+3x-3y)(5x+5y-3x+3y)=(8x+2y)(2x+8y)
                      =4(4x+y)(x+4y)
4(bc-a)²-9(a)²=(2bc-2a)²-(3a)²=(2bc-2a+3a)(2bc-2a-3a)=(2bc+a)(2bc-5a)
HOPE THIS HELPS U

2 4 2
hey can u solve this .....find the value of x in the following : (a) 32^x=8 (b) 5^x-3=1/25
32^x=2^5x=8=2^3
5x=3,x=3/5
5^x-3=1/25=5^(-2),x-3=-2,x=1
thnkuu so much ......
2015-01-16T12:22:37+05:30
(a) Given expression is a²b² - c²
This can be rewritten as (ab)² - (c)²
The identity can be used here is a²-b²  (a+b)(a-b)
Therefore, a²b² - c² = (ab+c)(ab-c)

(b) 25(x+y)² - 9(x-y)²
This can be rewritten as [5(x+y)]² - [3(x-y)]²
The identity can be used here is a²-b²  (a+b)(a-b)
Therefore, 25(x+y)² - 9(x-y)² = [5(x+y) + 3(x-y)][5(x+y)-3(x-y)]
On simplification,                   = [5x + 5y + 3x  - 3y] [5x + 5y - 3x + 3y]
                                              =  [8x + 2y] [2x + 8y]

(c) 4(bc-a)
² - 9a²
This can be rewritten as [2(bc-a)]² - (3a)²
The identity can be used here is a²-b²  (a+b)(a-b)
Therefore, 4(bc-a)² - 9a² = [2(bc-a) + 3a] [2(bc-a) - 3a]
On simplification,             = [2bc - 2a + 3a] [2bc - 2a - 3a]
                                        = [2bc + a] [2bc - 5a]

0